The music of thought in the poetry of George Oppen and William Bronk - Weinfield, Henry (University of Iowa Press, 2009)
From his careful readings of George Oppen's and William Bronk's poetry to his fascinating examination of the letters they exchanged, Weinfield provides important aesthetic, epistemological, and historical insights into their poetry and poetic careers. In bringing together for the first time the work of two of the most important poets of the postwar generation, The Music of Thought not only illuminates their poetry but also raises important questions about American literary history and the categories in terms of which it has generally been interpreted.